Analysis of Volleyball Extracurricular Service Skills: - Fauzi, M. Riki; Perdinanto; Anggara, Norma (Universitas PGRI Palembang, 2025)
Volleyball is a recreational, interesting, and cost-effective team sport, played by two teams of six people each, and can be carried out indoors or outdoors. The main goal is to keep the ball moving through the net into the opponent's area. This study uses a quantitative descriptive method with a survey approach and data collection techniques in the form of tests. This study does not examine the relationship between variables, but only focuses on one independent variable. The single variable in this study is volleyball serving skills, which is interpreted as the ability of students to serve consistently to support the achievement of game goals effectively and efficiently, so that this skill is an important indicator in assessing the mastery of basic techniques of volleyball among students. This study was conducted for 2 days with 10 repetitions of services for extracurricular students at SMPN 3 Batumandi. Based on the findings of the research on the upper service skills possessed by 12 students of SMPN 3 Batumandi, it is known that as many as 4 people (33%) showed ability in the good category with a score range between 21 to more than 41. A total of 6 people (50%) were in the sufficient category with a score range of 13 to 40, while 2 people (17%) were classified as in the poor category with a score range between 3 to 26. From the results of the distribution, it can be concluded that the majority of students who participated in volleyball extracurricular activities at SMPN 3 Batumandi had upper service skills in the sufficient category, which was 50% of the total participants studied.